Vibration investigation for passenger car with different damping characteristics on car suspension system - Zulkifli, Nawawi (2012)
This thesis investigates the effect of vibration and vehicle body movements acting on the vehicle’s wheel due to the different damping characteristics of suspension systems. Three different damping characteristics damper named Absorber A, Absorber B and Absorber C was installed on the suspension system of the Proton Persona which was used as a test car. This test car was equipped with accelerometers and wire potentiometer sensor on the front and rear suspensions, gyroscopic, Global Positioning System (GPS) and connect with DEWEsoft software as a data acquisition. To study the effect of three different damper characteristics on suspension system, the ride comfort analysis and car body movement analysis were used to analyze the result during experimental testing. There were 7 maneuver testing experiment were performed including acceleration, engine braking, steady-state braking, steady-state cornering, single-lane change, slalom and bump testing experiment. Based on the results, comparison between the suspension damper characteristics due to the driving maneuvers and car movement were made and their performance also were ranked. Absorber A was the hardest damper as compared to Absorber C and Absorber B according to the damping constant value. The result showed that the best performance for car movement made by Absorber A then followed by Absorber C and Absorber B, while the best performance for ride comfort analysis was made by Absorber B followed by Absorber C and A. Meanwhile Absorber A showed the lowest values of car body movement analysis and Absorber C showed the lowest values of suspension ride comfort analysis during acceleration, engine braking, steady-state braking and steady-state cornering tests. Absorber A was suitable for a flat road driving while Absorber C was suitable for a large road disturbance driving.